Radial Nerve Palsy Due to Blood Pressure Cuff Compression after Prolonged Combined Plastic Surgery - Thendo T. Netshiongolwe, MBChB, MMED, FC Plast Surg (SA) (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. As plastic surgery procedures become safer and more popular, the number of patients undergoing cosmetic surgery will rise. A recent trend in plastic surgery has been a rise in combining multiple procedures in a single setting. Such an approach has the advantage of lower surgical cost to the patient and affords the patient a reduced downtime from work. Although the complication profile of patients undergoing plastic surgery is well documented, combining procedures prolongs operation time, which has been associated with a significant increase in the risk of complications. Our case report describes a patient who presented with a wrist drop and paraesthesia in the radial nerve distribution 1 day postoperatively after prolonged combined breast reduction and abdominoplasty procedures. The patient was diagnosed with radial nerve neuropraxia through electromyography. She was reassured, treated by an occupational therapist and showed complete recovery within 3 months. Surgeons offering combined procedures for plastic surgery should be aware of the risk of nerve injury associated with prolonged blood pressure cuff monitoring and take precautionary measures to prevent this risk.